MOLECULAR CHARACTERIZATION OF RHIZOSPHERE BACTERIAL COMMUNITIES ASSOCIATED WITH WHEAT (TRITICUM AESTIVUM L.) CULTIVARS AT FLOWERING STAGE - I. Naz; M. S. Mirza; A. Bano (Journal of Animal and Plant Sciences, 2014)
There is limited knowledge available on rhizosphere bacterial communities associated with different cultivars. To contribute in this perspective the present research was conducted, based on 16S rRNA bacterial diversity in the rhizosphere soil of two wheat cultivars i-e Chakwal-50 and Fareed-06at flowering stage to investigate the hypothesis: cultivar difference affects the composition of rhizosphere bacterial communities. The 16S rRNA gene was amplified by 27 forward and 1492 reverse primers and cloned using TA cloning vector. The plasmid DNA of transformants was subjected to RFLP analysis by Hind III, X BaI restriction enzymes and sequenced by M13 Forward and Reverse primers. The results revealed heterogeneity in the bacterial communities of both rhizosphers that may correlates to variation in N- NO3, Mn, Fe and Co contents, soil moisture contents, total organic carbon and organic matter of rhizosphere soil. The two 16S-rRNA rhizosphere libraries covered 8 phyla, 14 classes, 14 orders, 23 families, 33 genera along with un-classified and un-characterized lineages that may represents novel lineages. At phylum, class, order, family and genera level 13, 50, 36, 78, 91 % divergence was observed. The sequence results confirmed the presence of beneficial bacteria in rhizosphere soil that are potentially effective for plants and soil health.
Keywords: Rhizosphere soil; Wheat cultivars; 16S rRNA gene library; TA cloning vector; RFLP.